Application of Lactic Acid Bacteria in Fermentation Processes to Obtain Tannases Using Agro-Industrial Wastes - García Méndez, Martha Gabriela; Morales Martínez, Thelma Karina; Ascacio Valdés, Juan Alberto; Chávez González, Mónica Lizeth; Flores Gallegos, Adriana Carolina; Sepúlveda, Leonardo (Fermentation (Basel), 2021)
Bacteria have been used in the food industry to produce flavors, dyes, thickeners, and to increase food value, because bacterial fermentations favor the obtention of different metabolites such as tannins and different nutritional compounds in food. Lactiplantibacillus plantarum was one the first species to be studied for industrial purposes, and its efficacy to obtaining tannins using fermentation processes. Bacterial fermentation helps to obtain a product with an added value of better quality and without the need to use strong solvents that can reduce their quality and safety. To release tannins, it is necessary to subject the substrate to different conditions to activate the enzyme tannin acyl hydrolase (tannase). The tannase-released compounds can have beneficial effects on health such as antioxidant, anticancer and cardioprotective properties, among others. Therefore, this review analyzes tannase release and other metabolites by fermentation processes.